2012
DOI: 10.1136/sextrans-2012-050601a.18
|View full text |Cite
|
Sign up to set email alerts
|

O18 Sexual behaviour, partnership patterns and STI diagnoses among HIV positive MSM: implications for HIV/STIs transmission and partner notification

Abstract: Background HIV infection continues to disproportionately affect MSM in the UK. The 2011 HPA report "Sexually Transmitted Infections in MSM in the UK" highlights the need for one-to-one behavioural interventions. Thus, identifying those at highest risk is essential. Aims To profile the sexual behaviour of younger MSM attending a dedicated clinic. To establish how MSM perceive their sexual risk and explore the use of a simple HIV Risk Assessment Tool (HIVRAT). Methods MSM attending a weekly clinic offering HIV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is also indicated by other studies that suggested that the consequences of the costs of disclosure might impede PN. 40 42 To say that a factor is “important” in one’s decision to disclose is slightly different from saying one expected this to be a consequence of disclosure. For example, the consequence, “we get closer”, might be an important for PLWH deciding on whether to disclose their status, but they might not expect to feel closer to their partner after making that disclosure in reality because their relationship was not close.…”
Section: Discussionmentioning
confidence: 99%
“…This is also indicated by other studies that suggested that the consequences of the costs of disclosure might impede PN. 40 42 To say that a factor is “important” in one’s decision to disclose is slightly different from saying one expected this to be a consequence of disclosure. For example, the consequence, “we get closer”, might be an important for PLWH deciding on whether to disclose their status, but they might not expect to feel closer to their partner after making that disclosure in reality because their relationship was not close.…”
Section: Discussionmentioning
confidence: 99%
“…Stances on disclosure and individual responsibility showed the dual burden criminalisation leads to. Disclosure was a feared moment (e.g., rejection) and fear of criminalisation was seen as a barrier to the disclosure of HIV status to potential sexual partners [47,51]. By contrast, disclosure was sometimes viewed as the responsibility of the person living with HIV (the onus of not transmitting HIV to a partner) rather than for the partner to take action to protect themselves [43,44].…”
Section: People Living With Hivmentioning
confidence: 99%
“…However, serosorting based on HIV status may increase rates of STIs as gbMSM may forgo condoms with the same HIV serostatus partners, concentrating STI rates among HIV-positive gbMSM [ 3 ]. Moreover, higher rates of serodiscordant condomless anal sex (CAS) are reported among HIV-positive gbMSM compared to HIV-negative gbMSM [ 4 ], with serodiscordant CAS identified as the main factor in STI diagnoses among HIV-positive among gbMSM [ 5 ]. Within Canada, a study of gbMSM living with HIV found an increased risk of chlamydia and gonorrhea was associated with multiple HIV-positive partners as well as recreational drug use [ 6 ].…”
Section: Introductionmentioning
confidence: 99%